2009
DOI: 10.1111/j.1740-0929.2009.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean hull supplementation to finishing pigs on the emission of noxious gases from slurry

Abstract: Ninety six pigs were assigned on the basis of body weight (BW) to one of four dietary treatments (4 pigs per pen and 6 pens per treatment) and fed for 4 weeks. Four 14.85% CP diets were formulated to contain graded levels of soybean hulls at 0, 5, 10, or 15%, respectively. The results showed that treatments did not affect growth performance. Coefficient of total tract apparent digestibility (CTTAD) for dry matter (DM) and blood urea nitrogen (BUN) concentrations were decreased linearly (P < 0.05) with the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…Evaluating different inclusion levels (0, 5, 10 and 15%) of Soybean hulls in diets for pigs, Wang et al (2009) pointed out that this by-product does not affect animal performance corroborating the results reported by Kornegay (1981) and Van Oeckel et al (1998). Nevertheless, DeCamp et al (2001 concluded that 10% inclusion of Soybean hulls in finishing swine diets increased ADFI and improved FCR of the animals since diets are supplemented with an energy source such as Soybean oil.…”
Section: Discussionsupporting
confidence: 76%
“…Evaluating different inclusion levels (0, 5, 10 and 15%) of Soybean hulls in diets for pigs, Wang et al (2009) pointed out that this by-product does not affect animal performance corroborating the results reported by Kornegay (1981) and Van Oeckel et al (1998). Nevertheless, DeCamp et al (2001 concluded that 10% inclusion of Soybean hulls in finishing swine diets increased ADFI and improved FCR of the animals since diets are supplemented with an energy source such as Soybean oil.…”
Section: Discussionsupporting
confidence: 76%
“…After the collection period, feces and urine samples were pooled and each mixed well for each pen. As described by Wang et al, subsamples of the slurry (150 g feces and 150 g of urine were mixed well; 1:1 on the wet weight basis) were taken and stored in 2.6-L plastic boxes in duplicate [19]. Each box had a small hole in the middle of one sidewall, which was sealed with adhesive plaster.…”
Section: Sampling and Measurementsmentioning
confidence: 99%
“…Previous studies have demonstrated that dietary nonstarch polysaccharides (NSP) supplementation could reduce manure N excretion and noxious gas production (Canh et al, 1997;Mroz et al, 2000;Wang et al, 2009). Flickinger et al (2003) reported that supplementation with 1.9 g/d of fructooligosaccharides tended to decrease fecal NH 3 concentration in dogs.…”
Section: Excreta Noxious Gas Emissionmentioning
confidence: 99%